Impedance-Based Inter-Turn Fault Diagnosis in Integrated Induction Motor and Drive Systems Using Space Voltage Vectors - Jungho Ahn; Ju Lee; Hyunwoo Kim (Applied Sciences)
In this paper, a winding inter-turn fault (ITF) diagnosis algorithm for electrical machines in integrated motor and drive (IMD) systems is proposed based on impedance analysis using space voltage vectors. An ITF alters the stator resistance, causing an imbalance in the motor’s impedance depending on the phase connection. This impedance asymmetry can be effectively utilized for fault diagnosis. However, in IMD systems, direct impedance measurement through mechanical terminal access is difficult due to the integrated structure. To address this, the impedance of the induction motor is analyzed electrically, without the need for physical disconnection, allowing practical implementation within integrated systems. The specific phase angle of the space voltage vector in the three-phase inverter is analyzed to replicate the electrical conditions of mechanical terminal configurations. Based on this approach, a fault diagnosis algorithm was developed by analyzing the variation in stator current and impedance with respect to space voltage vector angles. The effectiveness of the proposed method was verified through experimental validation using a 12kW three-phase induction motor and terminal box.